2011
DOI: 10.1101/gr.122358.111
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNA gene silencing through genomic integration of RNA destabilizing elements using zinc finger nucleases

Abstract: Zinc finger nucleases (ZFNs) allow site-specific manipulation of the genome. So far, the use of ZFNs to create gene knockouts has been restricted to protein-coding genes. However, non-protein-encoding RNAs (ncRNA) play important roles in the cell, although the functions of most ncRNAs are unknown. Here, we describe a ZFN-based method suited for the silencing of protein-coding and noncoding genes. This method relies on the ZFN-mediated integration of RNA destabilizing elements into the human genome, e.g., poly(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
146
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(152 citation statements)
references
References 36 publications
(48 reference statements)
1
146
0
3
Order By: Relevance
“…To generate the CMV-cGFP-mMALAT1_39 expression constructs, we modified a previously described plasmid (Gutschner et al 2011) in which the CMV promoter and the cGFP ORF were cloned into the multicloning site of the pCRII-TOPO vector (Life Technologies). Downstream from cGFP, we inserted the mMALAT1_39 region (nucleotides 6581-6754 of GenBank accession no.…”
Section: Expression Plasmid Constructionmentioning
confidence: 99%
“…To generate the CMV-cGFP-mMALAT1_39 expression constructs, we modified a previously described plasmid (Gutschner et al 2011) in which the CMV promoter and the cGFP ORF were cloned into the multicloning site of the pCRII-TOPO vector (Life Technologies). Downstream from cGFP, we inserted the mMALAT1_39 region (nucleotides 6581-6754 of GenBank accession no.…”
Section: Expression Plasmid Constructionmentioning
confidence: 99%
“…Emerging technologies for genome editing with engineered nucleases, such as zinc finger nucleases (ZFNs) and transcription activator-like effector nucleases, and oligonucleotide-directed methods represent stateof-the-art gene therapy techniques that can be used to target lncRNAs. For example, one study reported that the NEAT2 lncRNA could be silenced in human cells very effectively with ZFNs designed to insert RNA destabilizing elements into its gene locus biallelically [100]. Although this was a preliminary in vitro illustration, ZFN-based therapies are being studied in clinical trials for neurological diseases, including an adoptive T cell approach for glioblastoma (NCT01082926).…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…41 As a consequence lncRNA depletion that acts post-transcriptionally will not reveal a function, and these lncRNAs would require removal by homologous recombination in embryonic stem cells as described above for imprinted macro lncRNAs, or by zinc finger nucleases that can be used in any cell type. 105 Many studies have successfully used RNAi to knock-down spliced lncRNAs, 17,18,21,24,25,106 however it was not known if these were nuclear localized or exported to the cytoplasm. For example, a recent large-scale RNAi knockdown study which showed that 137 out of 147 lincRNAs had a significant effect on the expression of 100-200 genes in mouse embryonic stem cells, did not determine their nuclear or cytoplasmic localization.…”
Section: Cis-silencing Macro Lncrnas In Human Diseasementioning
confidence: 99%